Incidence and management of Bell’s palsy in peripheral facial paralysis cases - Gupta, Sucheta; Gupta, Vinod (International Journal of Research in Medical Sciences, 2022)
Background: The underlying pathophysiology observed in cases of Bell’s palsy is vascular distension, inflammation and oedema with ischaemia of the facial nerve. Various causes have been proposed including viral, inflammatory, autoimmune and vascular. The aim of this study was to evaluate the incidence and clinical presentation of Bell’s palsy among North Indian patients. Methods: A randomized prospective observational study was carried out in the department of otorhinolaryngology and head neck surgery, CHC, Chenani, Udhampur, on 60 patients, who presented with facial nerve palsy over a period of one year from August 2019 to July 2020. Patients were evaluated using the House-Brackman scale (HBS) and studied in relation to incidence, associated symptoms, percentage of recovery and effect of treatment on the rate of recurrence. Results: Of the 60 patients of facial nerve palsy, 44 patients were diagnosed of Bell’s palsy. 16 (37.5%) patients were grade II, 9 (14.6%) were grade III, 11 (31.3%) were grade IV, 7 (14.6%) were grade V and 1 (2.0%) patient was grade VI at onset. 21 (47.73%) patients had postauricular pain and 7 (15.90%) had hearing changes (phonophobia) during the attack. 35 (79.54%) patients recovered normal, while 9 (20.46%) patients did not return to normal life till the end of the follow up period. Out of the total 84.09% patients recovered, recurrence was also very low at 4.54%. Conclusions: A significant number of patients recovered fully from the condition; however, eye protection remains crucial in preventing long-term eye complications.